Microwave-assisted Synthesis of Zinc Oxide Nanoparticles. (2015) - Hasanpoor, M.; Aliofkhazraei, M.; Delavari, H.
Abstract: Synthesis of nanoparticles and ultrafine particles of zinc oxide with controlled morphology using microwave irradiation is carried out by various methods. The effect of type of precursor as well as the time and the microwave irradiation power on the structure and size of ZnO nanoparticles have been studied. Particles Studied by SEM, TEM images and XRD analyze. By increasing the time of synthesis from 10 to 15 minutes needle-shaped particles with a diameter of 50-150 nm can be achieved. While increasing the microwave power from 540 to 680 watts, flower-shaped particles are obtained. By replacing zinc nitrate with zinc acetate, at different power and time of irradiation, needle-shaped particles are obtained and diameter of needles is decreased.